The residual risk in cardiovascular diseases - Czarnecka, Danuta; Klima, Łukasz (Przewodnik Lekarza/Guide for GPs, 2009)
Dyslipidaemia, beside hypertension, diabetes and smoking, is recognized as one of the most important risk factors of cardiovascular diseases. Lowering of LDL cholesterol to the level recommended by societies of cardiology leads to significant reduction of major cardiovascular events. Nevertheless, patients are still exposed to remaining residual risk. Atherogenic dyslipidaemia, which is connected with residual risk, can be found significantly more often among diabetic patients and those with metabolic syndrome. Therapy with statins does not influence the risk connected with elevated triglycerides and lowered HDL cholesterol sufficiently, and a newly created international enterprise named the Residual Risk Reduction Initiative (R3i) aims to reduce residual risk by conducting clinical trials and analyzing available data, then recommending guidelines.